(untitled) (Web of Teachers: Inderscience Research, 2026)
This article explores effective ways to improve the efficiency of attracting foreign direct investment (FDI) as a key driver of sustainable economic growth. The study analyzes institutional, regulatory, and economic factors that influence the quality and effectiveness of FDI inflows. By applying analytical and comparative approaches, the paper identifies major constraints limiting investment efficiency and highlights policy mechanisms aimed at enhancing the investment climate and maximizing the developmental impact of foreign direct investment.